2019
DOI: 10.26480/mjsa.01.2019.13.19
|View full text |Cite
|
Sign up to set email alerts
|

An Overview Malaysia as a Hub of Planting Prophetic Fruits

Abstract: Only a small number of farmers involve in planting prophetic fruits such as dates palm, figs, pumpkin and watermelon in Malaysia. If look at Malaysia, Muslim is the majority population and practices Prophet Muhammad (pbuh) is a sunnah in order to gain benefit at the end of the day as a Muslim. There is a potential for Malaysian to plant and produce these prophetic fruits due to it availability in small scale. The main purpose of this study is to provide an overview of Malaysia as a hub of planting the propheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…, 2021). In addition, a continuous effort has been exerted to develop the rural areas by emphasizing on tropical fruits plantation (Kamarubahrin et al., 2019). This is consistent with the health-conscious trend among Malaysian (Durai, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). In addition, a continuous effort has been exerted to develop the rural areas by emphasizing on tropical fruits plantation (Kamarubahrin et al., 2019). This is consistent with the health-conscious trend among Malaysian (Durai, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia is one of the world's leading exporters of tropical fruits. Malaysia, as the world's largest producer of durian, mangosteen, and starfruit, produced 1.49 million metric tonnes in 2017 and exported roughly 268,400 metric tonnes [1] . Fruits were the most often purchased organic DOI: https://doi.org/10.30564/jeisr.v4i1.4585 food by Malaysian consumers, according to a survey done by Wong & Aini in Klang Valley [2] .…”
Section: Introductionmentioning
confidence: 99%
“…As in 2017, pumpkin plantations in Malaysia are mostly located in Kelantan, Terengganu, and Pahang, covering around 1531.36 hectares of the pumpkin-producing area [5]. Kamarubahrin [6] studied Malaysia's overview as prophetic fruits planting hub and reported that Malaysia grows up its pumpkin with considerably large areas of production to meet the increasing global demand. However, pumpkin is still considered an underutilized crop in Malaysia.…”
Section: Introductionmentioning
confidence: 99%